(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This doctoral study, Mughals at War: Babur, Akbar and the Indian Military Revolution, examines the transformation of warfare in South Asia during the foundation and consolidation of the Mughal Empire. It emphasizes the practical specifics of how the Imperial army waged war and prepared for war—technology, tactics, operations, training and logistics. These are topics poorly covered in the existing Mughal historiography, which primarily addresses military affairs through their background and context cultural, political and economic. Mughal emperor Akbar implemented many policies during his reign, which also included ’The Mughal Policy’. Abul Fazl says that in order “to soothe the mind of the zamidars, he entered into matrimonial relation with them”. In course of time, Akbar expanded and elaborated this policy. The Mughal were the greatest obstacle in his pursuance of policy against the Hindus. Aurangzeb attempted to destroy the power of the Mughal and annex their kingdoms. The mutual relations of the Mughals and the Rajputs have a great importance in the history of the Mughal period.